Strategi Guru PAI dalam Menerapkan Kedisiplinan Shalat Siswa SD IT Mutiara Kota Pariaman - Bella Shantika; Rahmi Wiza (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The strategies used by Islamic education teachers can create students who are disciplined in praying. The title of this research is